1986
DOI: 10.3758/bf03197015
|View full text |Cite
|
Sign up to set email alerts
|

Word and picture identification: Is representational parsimony possible?

Abstract: Four experiments were conducted to evaluate the proposition that although prior exposure to a printed word facilitates identification of a corresponding picture, exposure to a picture does not facilitate subsequent word recognition (Durso & Johnson, 1979).Word identification was used, rather than naming latency, in order to avoid the range limitations in adult reading data. Word identification was facilitated by intermodal priming (prior exposure to a corresponding picture), although to a lesser extent than by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
29
0

Year Published

1987
1987
2000
2000

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 42 publications
(46 reference statements)
3
29
0
Order By: Relevance
“…Studies have shown strong within-modality repetition effects for both pictures and words (i.e., facilitation from having previously encountered the same concept in the same modality; e.g., Durso & Johnson, 1979;Kirsner, Milech, & Stumpfel, 1986;Warren & Morton, 1982) and generally weaker cross-modality repetition effects (e.g., Durso & Johnson, 1979;Kirsner et al, 1986;Scarborough, Gerard, & Cortese, 1979;Warren & Morton, 1982). Further converging evidence, such as cross-modality facilitation effects in associative priming (e.g., Carr, McCauley, Sperber, & Parmalee, 1982;Guenther, Klatzky, & Putnam, 1980;Sperber, McCauley, Regain, & Weil, 1979;Vanderwart, 1984), supports the view that (I) pictures and words access a common semantic representation and (2) pictures access this semantic representation directly from a structural representation, whereas words may access the semantic representation either directly (from an orthographic input representation) or indirectly after some amount of phonological processing has occurred (e.g., Bajo, 1988;M.…”
Section: Priming Modality and Task Influences On Object Namingmentioning
confidence: 99%
“…Studies have shown strong within-modality repetition effects for both pictures and words (i.e., facilitation from having previously encountered the same concept in the same modality; e.g., Durso & Johnson, 1979;Kirsner, Milech, & Stumpfel, 1986;Warren & Morton, 1982) and generally weaker cross-modality repetition effects (e.g., Durso & Johnson, 1979;Kirsner et al, 1986;Scarborough, Gerard, & Cortese, 1979;Warren & Morton, 1982). Further converging evidence, such as cross-modality facilitation effects in associative priming (e.g., Carr, McCauley, Sperber, & Parmalee, 1982;Guenther, Klatzky, & Putnam, 1980;Sperber, McCauley, Regain, & Weil, 1979;Vanderwart, 1984), supports the view that (I) pictures and words access a common semantic representation and (2) pictures access this semantic representation directly from a structural representation, whereas words may access the semantic representation either directly (from an orthographic input representation) or indirectly after some amount of phonological processing has occurred (e.g., Bajo, 1988;M.…”
Section: Priming Modality and Task Influences On Object Namingmentioning
confidence: 99%
“…Such frequency effects on priming have been obtained in lexicaldecision tasks, perceptual-identification tasks, and wordfragment completion tasks (Jacoby & Dallas, 1981;Kirsner, Milech, & Stumpfel, 1986;MacLeod, 1989;Scarborough, Cortese, & Scarborough, 1977). However, these effects of frequency on priming often are small and not statistically significant.…”
mentioning
confidence: 99%
“…Across several experiments, Weldon and colleagues (Roediger et al, 1992;Weldon, in press;Weldon & Roediger, 1987;Weldon et al, 1989) have repeatedly found that although words produce substantially more priming than do pictures on this test, pictures consistently produce small but significant amounts of priming (about .20 for words, .05-.07 for pictures). Others also have obtained significant priming from pictures on verbal, perceptual tasks (Brown, Neblett, Jones, & Mitchell, 1991;Kirsner, Milech, & Stumpfel, 1986;Kroll & Potter, 1984). Pictures provide an interesting means for studying priming on the word-fragment completion test because they share no physical features with the target words yet still refer to the same concept.…”
mentioning
confidence: 99%